Managing disruption at a distance: Unequal experiences of people living with long-term conditions during the COVID-19 pandemic. (June 2022) - Morris, Stephanie; Wildman, Josephine M.; Gibson, Kate; Moffatt, Suzanne; Pollard, Tessa M.
Abstract: The COVID-19 pandemic and 'lockdown' restrictions have affected people's health and wellbeing globally. Those who are clinically vulnerable to COVID-19 mortality due to living with long term conditions (LTCs) are at greater risk of negative impacts on their health and wellbeing, and of disruption in management of their LTCs. This study explores how people with LTCs managed their health and wellbeing under social distancing restrictions and self-isolation during the first wave of the COVID-19 pandemic, and examines why some people were more able to manage than others. Interviews were conducted between May and July 2020 with people (n = 44) living in North East England, who had one or more LTCs and were recruited via a social prescribing intervention. Data were analysed using a social constructivist thematic analysis. We present our analysis of the possibilities afforded to people to manage the impacts of lockdown on their health and wellbeing. We find that while some people deployed a range of capitals and/or etched out 'tactics' to make life 'habitable', others experienced 'zones of impossibility' requiring that they rely on contingent events or formal support. Our analysis highlights inequalities amongst people with LTCs, particularly regarding access to and deployment of important resources for health and wellbeing under COVID-19 social distancing restrictions, including outdoor space or greenspace, exercise and social connection. The study is novel in showing the mechanisms for coping with a significant period of disruption in the life-course whilst highlighting that although resilience was common in people with LTCs, this was sometimes at detrimental costs to themselves. Highlights: There were inequalities in how people with long-term conditions (LTCs) coped during the first wave of the COVID-19 pandemic. Social position and access to resources were important for coping during the pandemic. Outdoor space or greenspace, physical activity and social connection were key for managing health and wellbeing. People with LTCs attempted resilience sometimes at detrimental costs to themselves.